Informacja o zbiorach dawnego Muzeum Księży Marianów im. ks. Józefa Jarzębowskiego w Fawley Court (Wielka Brytania) – obecnie w Muzeum im. ks. Józefa Jarzębowskiego w Licheniu Starym koło Konina. - Maria Wrede; Maria Brynda; Zofia Głowicka (Z Badań nad Książką i Księgozbiorami Historycznymi, 2020)
History of the Museum of Marian Fathers, founded at the college for boys in Bielany, the district of Warsaw, reconstituted in the Fawley Court at Henley-on-Thames, Great Britain, and finally moved to the Shrine of Our Lady of Sorrows in Licheń Stary, is the key to understanding the content and organization of this collection. Patriotic, religious and educational aspects of the museums, its role for the Polish diaspora in Great Britain, and its depletion in the results of historical changes. Presentation of the collection content” museum objects – sidearm, sculptures, artistic fabrics, drawings and watercolors, paintings, graphics, commemorative items; book collection – books from the 19th and 20th centuries, journals, music prints, maps, and cityscapes. A more detailed presentation of the collection of early printed books, ephemera, and journals from the 19th century.